Stratigraphic evolution of a Late Triassic to Early Jurassic intracontinental basin in southeastern South China: A consequence of flat-slab subduction - Pang, Chongjin; Krapez, Bryan; Li, Zheng-Xiang; Xu, Y.; Liu, H.; Cao, J. (Elsevier Science BV, 2014)
An intracontinental basin formed on a young orogen in South China during the Late Triassic to Early Jurassic (T3–J1). A >2000 m-thick siliciclastic sedimentary succession in the Daxi section, in northern Guangdong Province, near the depocentre of the basin, is correlated with the published Zhuyuan section and three other sections. The combined Daxi–Zhuyuan sections record a marine-influenced deltaic succession of Carnian to Early Toarcian age, spanning a period of ~55 Myr. Tectonic controls, rather than eustasy and climate, are interpreted to have played a primary role in the cyclic development of the basin fill. Four regional-scale tectonostratigraphic stages are recognised. Stage 1 features a retrogradation–progradation cycle characterised by increasing then slowly decreasing subsidence rates, accompanied by slow to medium sedimentation rates. Stage 2 is broadly an aggradational cycle with multiple smaller-scale retrogradational–progradational cycles. A complex interplay between moderate subsidence rates, high sedimentation rates and eustasy is interpreted for this stage. Stage 3 represents a retrogradational–aggradational–progradational cycle during which the impact of global sea level was much reduced. This period was characterised by mostly high sedimentation and high subsidence rates, but a change to lower subsidence and sedimentation rates took place prior to the intracontinental uplift that inverted the basin. Stage 4 records continued uplift and the subsequent development of a Late Jurassic–Cretaceous basin-and-range province. The temporal–spatial evolution of the basin could be best explained by the gravitational pull of a subducted flat-slab and its subsequent foundering.